EXPRESSION OF CONCERN: Research on Portable Intelligent Terminal and APP Application Analysis and Intelligent Monitoring Method of College Students' Health Status - Li, Yu; Gao, Yuetong (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12709
Keywords: portable intelligent terminal APP application analysis; intelligent detection of university students' health status; attention mechanism; gated recurrent unit neural network; intelligent optimisation algorithm